Prediction of 305-day first lactation milk yield by ratio method - SINGH, SHANKER; TAILOR, S P (The Indian Journal of Animal Sciences, 2014)
First lactation milk records from 1976 to 2004 on 453 buffaloes, sired by 51 bulls, maintained at Network Project on Buffalo, Livestock Research Station, Vallabhnagar were utilized for prediction of 305-day first lactation milk yield (305 FLMY). The milk production levels were predicted from records in progress (fortnightly, monthly and bimonthly test as well as part yields) using ratio method. Sampling schemes, viz. systematic and stratified random sampling schemes were used. The maximum R2 was obtained during 10th and 11th fortnight and minimum during the first fortnight when lactation milk yield was predicted on the basis of fortnightly systematic and stratified random sampled test records as well as part yields. Similarly, accuracy was the maximum when test sample was taken during sixth month and minimum when test sample was taken during first month. The accuracy of prediction of lactation yield on the basis of monthly part yields showed that maximum (62.25%) accuracy was obtained for fifth month and minimum (29.27%) during first month, which is higher than accuracies obtained under both systematic and stratified random sampling schemes. The maximum (47.20 and 46.38% respectively) accuracy for prediction was obtained when test sample was taken during third bimonth and minimum (35.76 and 29.59% respectively) during first bimonth. The prediction based on bimonthly part yields revealed that maximum (66.42%) accuracy was obtained during third bimonth and minimum (51.70%) accuracy during first bimonth. Looking at the cost of recording under field conditions and computational difficulties, a single test record could be taken during 10th fortnight and sixth month by systematic and 11th fortnight by stratified random sampling schemes gave predictability more than 50% for prediction of 305 days first lactation milk yield by ratio method.